Transfer : Austausch bildender Künstler und Kunst 2000/2001. - Schmidt, Dietmar N; Klement, Carmen; Argumedo, José Maria; Wuppertal (Wuppertal : Kultursekretariat Nordrhein-Westfalen, 2000)
Anleo, Xoán ; Troyas, Ricardo anton ; Barreiro, Alberto ; Blanco, Vicente ; Braun, Alexander ; Formanek, Mark ; von Gizycki, Mirko ; Gracenea, Inaki ; Grölle, Jürgen ; Hoderlein, Stefan ; Lempert, Jochen ; de Lillo, Pablo ; et al.
Centro Galego de Arte Contemporanea, Santiago de Compostella, 22.09.2000-12.11.2000 / Centro Cultural Cajastur, Palacio Revillagigedo, Gijon, 23.11.2000 - 21.01.2001 / Sala de Exposiciones REKALDE, Bilbao, 08.02.2001 - 25.03.2001 / Städtisches Museum Leverkusen Schloss Morsbroich, 18.05.2001 - 22.07.2001 / Wilhelm Lehmbruck Museum Duisburg, 19.05.2001 - 22.07.2001 / Städtisches Museum Abteiberg Mönchengladbach, 20.05.2001 - 22.07.2001 / Zollverein-Ausstellungen, Gesellschaft für zeitgenössische Kunst, Essen, 01.09.2001 - 21.10.2001
kunstcatalogus